2013
DOI: 10.1002/lt.23763
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic changes in the hepatic circulation after the modulation of the splenic circulation in an in vivo human experimental model

Abstract: Recent advances in liver surgery have highlighted the effects of the splenic circulation on the hepatic circulation with respect to the hepatic arterial buffer response (HABR). The aim of the present study was to investigate the actual hemodynamic effects of splenic artery embolization/ligation and splenectomy on the hepatic circulation in patients who underwent pancreaticoduodenectomy through in vivo experimental models. In vivo models of splenic artery embolization/ligation (only splenic artery clamping) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…First, selecting a larger graft can increase GSVR. [30][31][32] Therefore, it should be reserved for only necessary cases. Second, SPX could prevent thrombocytopenia and improve graft function.…”
Section: Discussionmentioning
confidence: 99%
“…First, selecting a larger graft can increase GSVR. [30][31][32] Therefore, it should be reserved for only necessary cases. Second, SPX could prevent thrombocytopenia and improve graft function.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that in these scenarios, vascular remodeling is driven by increased tangential shear stress over endothelial cells leading to increased expression of adhesion molecules, recruitment of inflammatory cells, and secretion of several mediators and cytokines that ultimately determine reshaping of the arterial wall and caliper measurement increases. After SA ligation, flow into the hepatic artery is increased as an effect of the interruption of the splenic siphon and of decreased portal vein flow . The flow is diverted also toward the LGA and, if the gastroduodenal artery has not been divided, toward the GEA, causing the hemodynamic changes determining vascular remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Although clinically different, portal hyperperfusion plays a pivotal role in both syndromes by determining vasoconstriction and disturbance of hepatic artery flow . SA occlusion has been shown to cause a modulation of portal vein flow and a concomitant increase of hepatic artery flow, and it has therefore been advocated as an effective procedure to prevent or treat both small‐for‐size syndrome and SA syndrome . In selected patients, the SA can be divided and used for arterial reconstruction during transplant operation if the hepatic artery and its branches are not suitable …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The following report by Feng et al shown the advantage of splenectomy which could prevent the occurrence of SFSS by leading a decrease in the portal flow and PVP and a significant increase in the arterial flow. 15,16 Nevertheless, there is also considerable increase of surgical risk and infection for splenectomy. 17,18 On the other hand, recent studies suggest spleen plays an important role in regulating the immune system, metabolism, and endocrine function.…”
Section: Discussionmentioning
confidence: 99%